PALEOMAGNETIC EVIDENCE ON THE GENESIS OF THE HARD HEMATITE ORE DEPOSITS OF THE VERMILION RANGE, MINNESOTA - Symons, D. T. A. (Canadian Journal of Earth Sciences, 1967)
Paleomagnetic measurements using standard methods were made on 55 samples of hard hematite iron ore and associated host rocks that were collected from along the surface exposure, and from underground in the Pioneer Mine at Ely and in the Soudan Mine at Soudan, on the Vermilion Range, Minnesota, U.S.A. The unaltered host rocks have a stable pre-folding remanence of probable Keewatin age, whereas the ore and adjacent altered host rocks have a stable post-folding remanence of possibly Early to Middle Keweenawan age. This result indicates that the ore originated as a post-folding epigenetic deposit.